51‐3: A Multi‐plane Optical See‐through Head Mounted Display with Reverse Mode PSLC. Issue 1 (May 2017) - Liu, Shuxin; Li, Yan; Zhou, Pengcheng; Huang, Shuaijia; Chen, Quanming; Su, Yikai
Abstract : In this paper we propose an optical see‐through head mounted display (HMD) for augmented reality display by utilizing reverse mode polymer‐stabilized liquid crystal (PSLC). The system has lower power consumption compared with our previous work which employs the normal mode PSLC. The HMD provides the depth information accurately and solves the accommodation‐vergence conflict problem caused in the conventional HMDs.